Associations between Smoking, Intrauterine Device Uptake, and Ectopic Pregnancy: A Meta Analysis - Yanuari, Ridha Rossela; Pamungkasari, Eti Poncorini; Widyaningsih, Vitri (Journal of Maternal and Child Health, 2021)
Background: Ectopic pregnancy is an important cause of maternal morbidity and mortality, estimated to occur in approximately 1-2% of pregnancies worldwide. Smoking and history of using intrauterine devices are risk factors for ectopic pregnancy. This study aims to estimate the magnitude of the relationship between smoking and a history of using intrauterine devices on the incidence of ectopic pregnancy based on a number of previous primary studies. Subjects and Method: This study is a systematic review and meta-analysis. The articles used in this study were obtained from several databases, including: PubMed, Google Scholar, and Science Direct which were published from 2000-2020. The inclusion criteria used are full text articles with Case Control design. The keywords used to search for articles were as follows: smoking AND "ectopic pregnancy" AND multivariate; "use of intrauterine device" AND "ectopic pregnancy" AND multivariate; smoking OR cigarette AND “use of intrauterine device” AND “ectopic pregnancy” OR “tubal pregnancy” AND multivariate. Articles were collected using PRISMA flow diagrams and analyzed using the Review Manager 5.3. Results: A meta-analysis of 7 articles showed that women of reproductive age who smoked had a 2.20 times risk of ectopic pregnancy compared to women of reproductive age who did not smoke (aOR= 2.20; 95% CI= 1.45 to 3.34; p= 0.002). A meta-analysis of 9 articles showed that women of reproductive age with a history of using intrauterine devices had a 2.28 times risk of ectopic pregnancy compared to women of reproductive age who did not use intrauterine devices (aOR= 2.28; 95% CI= 1.74 to 2.98; p<0.001). Conclusion: Smoking and a history of using intrauterine devices increase the risk of ectopic pregnancy.